Examining the Clearance Rates of Violent and Non-Violent Offences in the United States: A Trend Analysis, 2011–2018 - Avdija, Avdi S. (International journal of offender therapy and comparative criminology, 2021)
The main objective of this study was to examine the clearance rates of violent and non-violent offenses in the United States for the years 2011 to 2018. This study focused specifically on the differences in clearance rates of incidents involving crimes against persons, crimes against property, and crimes against society. The analyses are based on the FBI’s NIBRS data that have been reported by local, state, and federal law enforcement agencies for 8 years combined. The analyses focused on the characteristics of the distribution of clearance rates by the types of incidents. The clearance rates were calculated based on the number of incidents that were cleared by arrest or exceptional means. The results show that the average clearance rate for incidents involving crimes against persons is 48.6%, for incidents involving property crimes is 18%, and for incidents involving crimes against society is 78%. The trend analyses show that the clearance rates are gradually decreasing for all three types of offense categories.